2014
DOI: 10.1021/ie502193e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Silica-Encapsulated Iron, Cobalt, and Ruthenium Nanocatalysts for Fischer–Tropsch Synthesis in Silicon-Microchannel Microreactors

Abstract: Fischer–Tropsch (FT) synthesis in Si-microchannel microreactors, containing 116 channels (50 μm × 100 μm × 1.3 cm), was carried out using SiO2-encapsulated Fe, Co, and Ru catalysts. The microchannels were uniformly coated with catalyst via a modified closed channel infiltration (mCCI) procedure. The mCCI method helps to load the catalyst without blockage of channels with no issues related to anodic bonding. The catalysts were characterized by scanning electron microscopy, optical microscopy, energy-dispersive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…The syngas used in our studies is a mixture of ultrahigh pure 5.0 CO and H 2 gases; therefore, there is very little or no chance of catalyst deactivation due to poisoning by the gas feed at the inlet to the reactor. It was also observed in our previous studies that the support (SiO 2 vs TiO 2 ) can enhance the stability of the catalyst to resist deactivation [38,40]. Iglesia et al, noticed that silica supported materials are less stable when compared to the other supports like Al 2 O 3 [100] in their FT studies with Co-based catalyst.…”
Section: Fabrication Of Microreactorsupporting
confidence: 54%
See 1 more Smart Citation
“…The syngas used in our studies is a mixture of ultrahigh pure 5.0 CO and H 2 gases; therefore, there is very little or no chance of catalyst deactivation due to poisoning by the gas feed at the inlet to the reactor. It was also observed in our previous studies that the support (SiO 2 vs TiO 2 ) can enhance the stability of the catalyst to resist deactivation [38,40]. Iglesia et al, noticed that silica supported materials are less stable when compared to the other supports like Al 2 O 3 [100] in their FT studies with Co-based catalyst.…”
Section: Fabrication Of Microreactorsupporting
confidence: 54%
“…Therefore, the selection of support and study of its interaction with the incorporated metal ion plays an important role in catalysis. In our previous studies, sol-gel encapsulated catalysts were used in silicon microreactors for FT synthesis [37][38][39]. While Al 2 O 3 and SiO 2 sol-gel supports show similar behavior in formation of higher alkanes such as ethane, propane, and butane for the reactions at 1 atm, TiO 2 has a profound effect on FT synthesis [40] and the stability of the catalysts are observed in reverse order from that observed with SiO 2 and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 97%
“…The FT process is also used as an indirect route for GTL processes. This is where syngas is converted to hydrocarbons in the presence of an iron or cobalt catalyst 13 . The preferred catalyst of choice is Cobalt for the low temperature FT (LTFT) process.…”
Section: Ch 4 + Hmentioning
confidence: 99%
“…Consequently, field installation takes place faster and the overall capital investment of the project is considered more lucrative than typical installations. Furthermore, overall project capital utilisation can be improved by adding or removing microreactor components to increase or eliminate the plant capacity on an incremental basis [12][13] . Many studies have shown promising results for liquid fuel synthesis in microstructured reactors such as micro-channel reactors, packed bed microreactors and micro-plasma reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Among various factors which influence the product selectivity, temperature control in fixed bed reactors is more important due to the formation of hot spots which accelerates the methane formation and decreases the chain growth probability . Microchannel reactors (MCRs) provide the benefits of portability, easy scale-up, better heat and mass transfer characteristics, high reaction throughputs, precise control of hydrodynamics, and, when coated with multifunctional catalysts, they may also provide much improved product selectivity and yield. Mehta et al utilized silicon based microchannel reactors to synthesize hydrocarbons from syngas.…”
Section: Introductionmentioning
confidence: 99%